2005
DOI: 10.1029/2005gl023992
|View full text |Cite
|
Sign up to set email alerts
|

Can synthetic aperture radars be used to estimate hurricane force winds?

Abstract: We compare wind fields retrieved from a RADARSAT‐I synthetic aperture radar (SAR) image acquired over Hurricane Ivan on September 10, 2004 using the C‐band geophysical model functions Cmod4 and its newest version Cmod5. Cmod4 has previously been shown to yield very good wind field estimates under low and moderate wind conditions. Wind directions obtained from streaks imaged by the SAR, that are well aligned with the mean surface wind direction are used to invert both algorithms to obtain estimates of the wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 13 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…SAR-observed NRCS σ 0 is directly related to the sea surface roughness of short surface waves, and is widely used for ocean wind retrievals i.e., [32,44,45]. Thus, NRCS can represent information on wind sea (short wave roughness) and co-polarized (VV) NRCS has been introduced into SAR empirical SWH algorithms [19,20,23].…”
Section: Normalized Radar Cross Section (Nrcs)mentioning
confidence: 99%
“…SAR-observed NRCS σ 0 is directly related to the sea surface roughness of short surface waves, and is widely used for ocean wind retrievals i.e., [32,44,45]. Thus, NRCS can represent information on wind sea (short wave roughness) and co-polarized (VV) NRCS has been introduced into SAR empirical SWH algorithms [19,20,23].…”
Section: Normalized Radar Cross Section (Nrcs)mentioning
confidence: 99%
“…The definition of other parameters in Equations (1) to (8) can be found in Figure 1. The simulated brightness temperature data of group A in Figure 1a are the results under calm ocean conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Before estimating the model coefficients, we need to calculate the parameter 6(10)P − (P = V or H) with Equations (4) and (8). First, it need to estimate the calm ocean microwave emissions at both 6 and 10 GHz using Equations (10) and (11)…”
Section: Comparison Of the Klein-swift Model And The Ellison Modelmentioning
confidence: 99%
“…Du and Vachon (2003) developed a wavelet technology to extract hurricane eye information from eight Radarsat-1 SAR images. Limited case studies by Horstmann et al (2005) and Shen et al (2006) showed the capabilities of using single-polarization Radarsat-1 SAR for high-resolution wind speed mapping with existing geophysical model functions (GMF). Yang et al (2011) later showed that the wind retrieval accuracy is, however, highly sensitive to the NRCS calibration accuracy.…”
Section: The Abstract For This Article Can Be Found In This Issuementioning
confidence: 99%